Translation in Japan: The Cassette Effect - Yanabu, Akira (TTR)

(untitled) (Association canadienne de traductologie, 2009)
Japan has always exhibited a serious attitude towards the translation of foreign languages. Any discussion of this issue must take into account the fact that ancient Japan borrowed Chinese characters, called kanji, from China. In this paper, I will focus on the use of kanji in translation, which has rarely been discussed in Western Translation Studies. Since ancient times, the Japanese have read imported books written in kanji according to a method called kundoku, which is still used for reading Western languages in modern Japan. Kanji was also used for writing the Japanese language.This article deals primarily with examples of kanji used to translate Western words. Cultures that use kanji, including Japan, have long trusted its expressive ability, which is why Japanese translators used this so‑called ideogram. In modern times, Japanese translators have used kanji to express the meanings of Western words. Of course, this type of usage has its limits when trying to express meanings from other cultures. On the other hand, this method of translation is fairly efficient: although people reading a kanji may not at first understand its full meaning, they perhaps feel that it has a serious meaning that can be roughly understood from its context. I call the assumption of meaning triggered by kanji the “cassette effect.”